The Effect of Wall Shooting Drill Using B.E.E.F Method on Free Throw Accuracy in Senior High School Basketball Athletes - Silvia Alya Azizah; Fajar Syamsudin (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
This study aimed to determine the effect of wall shooting drill training using the B.E.E.F. method (Balance, Eyes, Elbow, and Follow-Through) on the free-throw accuracy of basketball athletes at SMAN 3 Tegal City. The study employed a quantitative approach with a quasi-experimental method using a one-group pre-test–post-test design. The sample consisted of 25 athletes selected through a total sampling technique. The treatment was administered over 12 training sessions within four weeks. Data were collected through free-throw tests conducted before and after the treatment. The data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, and a paired-samples t-test. The results showed that the mean free-throw score increased from 3.92 in the pre-test to 4.84 in the post-test. The paired-samples t-test revealed a significance value of 0.037 (p < 0.05), indicating a significant difference between the pre-test and post-test results. Therefore, it can be concluded that wall shooting drill training using the B.E.E.F. method has a significant effect on improving free-throw accuracy among basketball athletes. This method can be recommended as an alternative training program to enhance free-throw performance in school-level basketball athlete development.